Optimierte Disposition und Telematik steigern Effizienz im deutschen SGV. - Baumgartner, Michael; Léonardi, Jacques (Deutscher Verkehrs-Verl., 2004)
Viele Verkehrsfachleute vermuten, dass die negativen Auswirkungen des prognostizierten Güterverkehrswachstums auf Klima, Umwelt und den Verkehr selbst durch logistische Änderungen in den Transportprozessen abgeschwächt werden könnten. Der Beitrag zeigt auf, wie durch optimierte Disposition und den Einsatz von Telematik die CO2- und Treibstoffeffizienz von Straßengüterverkehrsunternehmen um 2 bis 10 % verbessert werden kann. difu

This survey covers the measures adopted by companies engaged in Germany's freight haulage-by-road. Which seek to enhance operational efficiency through optimum transport arrangements and the application of telematics. It focuses on the reduction of C02 emission, fuel efficiency and economic aspects. The introduction of a database system to support transport arrangements and of telematics to facilitate data exchange, vehicle positioning and navigation, has led freight forwarders achieving a CO2 efficiency factor (= fuel efficiency) of between two and ten per cent (with a medium estimated rate of eight per cent). A somewhat lower level of efficiency has been recorded in so far as distances are concerned. The various systems available tend to pay for themselves within a period of one to two and a half years, while the logistic systems offer companies the advantage of optimum operational transparency. All the 19 companies investigated have stated that they would not hesitate to install such system again. Utilizing databases in support of transport arrangements and telematics systems, Germany's freight haulage-by-road system, could achieve CO2 savings of between three and five per cent. difu
Keywords: Verkehr; Güterverkehr; Straßengüterverkehr; Effektivität; Verkehrsunternehmen; Untersuchung; Informationstechnologie; EDV; Kohlendioxid; Logistik; Telematik; Güterverkehrsmarkt